Statistical optimization of lactic acid production by Lactobacillus pentosus using hemicellulose hydrolysate from sugarcane bagasse - Wischral, Daiana (2018)
The present work reports investigation of hemicellulose hydrolysate from sugarcane bagasse as a sole carbon source for lactic acid production by Lactobacillus pentosus ATCC 8041. Initially, sugarcane bagasse was pretreated with acid in a solid:liquid ratio of 1:2.8 (1 g of bagasse: 2.8 mL of sulfuric acid solution 1 % v/v) at a temperature of 121 °C for 27 min. Then, concentration of both the hemicellulose hydrolysate and the yeast extract in MRS medium were optimized using Response Surface Methodology through software STATISTICA 6.0. Once the optimal conditions (40 % of hemicellulose hydrolysate and 5 g/L of yeast extract) were validated, fermentations were carried out in anaerobic conditions at 37 °C and 120 rpm. After 48 h, 19.17 g/L of lactic acid were produced, with yield of 0.80 g/g, corresponding to a volumetric productivity 0.40 g/(L*h). Findings of this work demonstrate that hemicellulose hydrolysate from sugarcane bagasse is a promising carbon source for lactic acid production.